Research Paper On Home Security System - Sahu, Sanatnu; Subudhi, Asit (International Journal of Psychosocial Rehabilitation, 2025)
With the development of social economy, more and more applications have been presented in a house thus decreasing security and privacy. It comes out a task that the way to manage and control these increasing numerous appliances efficiently and conveniently so as to achieve more comfortable, security and healthy space at home. The project proposes an efficient implementation for IoT (Internet of Things) used for observance and controlling the home appliances via World Wide Web. This IoT project focuses on building a smart wireless home security system which sends alerts to the owner by using Internet in case of any trespass and raises an alarm optionally. The leverage obtained by preferring this system over the similar sort of existing systems is that the alerts and the status sent by the Wi-Fi connected microcontroller managed system will be received by the user on his phone from any distance irrespective of whether his mobile phone is connected to the internet. The microcontroller used in the current prototype is the TI-CC3200 Launch pad board which comes with an embedded microcontroller and an onboard Wi-Fi shield making use of which all the electrical appliances inside the home can be controlled and managed.